Interaction of Mosquito’s hppd Enzyme with Lansoprazole Sulfide A New Hope to Tackle the Mosquito Menace – an in-Silico Study - Prakash Vaithyanathan (International Journal of Insects, 2026)
Tyrosine detoxification is an important physiological process that helps blood-feeding insects, such as mosquitoes that transmit Plasmodium parasites causing malaria, digest their blood meals. An enzyme known as 4-hydroxyphenylpyruvate dioxygenase (HPPD), which is part of the tyrosine detoxification pathway, helps in removing excess tyrosine in a high-protein blood meal. Excess tyrosine can be lethal to the insects, and hence, the role of HPPD enzyme is very critical. Inhibitors of HPPD enzyme have been used as herbicides, and it has been suggested that they can also be used to control the mosquito menace. For the first time, docking studies and molecular dynamics simulations have demonstrated that Lansoprazole sulfone or Lansoprazole sulfide, metabolites of Lansoprazole, can modulate the activity of the HPPD enzyme, which can be lethal to mosquitoes through its interaction with critical residues. In addition, a comparison with the HPPD modulating activity of theobromine's metabolite, 7-methyl xanthine, is also presented.
Keywords: HPPD; Keywords: 7-methyl xanthine; Lansoprazole sulfide; Lansoprazole sulfone; enzyme; mosquitoes; tyrosine detoxification